2017
DOI: 10.3390/antiox6010018
|View full text |Cite
|
Sign up to set email alerts
|

Na/K-ATPase Signaling and Salt Sensitivity: The Role of Oxidative Stress

Abstract: Other than genetic regulation of salt sensitivity of blood pressure, many factors have been shown to regulate renal sodium handling which contributes to long-term blood pressure regulation and have been extensively reviewed. Here we present our progress on the Na/K-ATPase signaling mediated sodium reabsorption in renal proximal tubules, from cardiotonic steroids-mediated to reactive oxygen species (ROS)-mediated Na/K-ATPase signaling that contributes to experimental salt sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 158 publications
(187 reference statements)
3
8
0
Order By: Relevance
“…Furthermore, MBG has been shown to regulate the permeability and gene expression of human brain microvascular endothelial cells in culture [31], increasing the interest in evaluating the possible role of MBG in cerebrovascular and other related vascular disease conditions. Recent studies have investigated the roles of MBG in angiogenic and stress signaling [32], modulation of oxidative stress [33] and neuroinflammation [11]. These findings support the earlier hypothesis that MBG activates endothelial NADPH oxidase [34].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Furthermore, MBG has been shown to regulate the permeability and gene expression of human brain microvascular endothelial cells in culture [31], increasing the interest in evaluating the possible role of MBG in cerebrovascular and other related vascular disease conditions. Recent studies have investigated the roles of MBG in angiogenic and stress signaling [32], modulation of oxidative stress [33] and neuroinflammation [11]. These findings support the earlier hypothesis that MBG activates endothelial NADPH oxidase [34].…”
Section: Discussionsupporting
confidence: 79%
“…The interaction of MBG at different concentrations with alpha 1 isoforms of the Na, K ATPase, its activation of the non-receptor tyrosine kinase Src by a sodium pump-evoked signal transduction and the activation of oxidant-sensitive enzymes also support the concept that MBG can induce endothelial oxidase stress. These findings contribute to the hypothesis that MBG may be a link between salt sensitivity, increased vascular mortality, and cardiovascular disease, including stroke [11,33,34].…”
Section: Discussionmentioning
confidence: 73%
“…Due to this, obese TH mice might be prone to developing hypertension when challenged with a high salt diet (Figure 3C and Figure 4B). In particular, Na/K-ATPase is highly sensitive to changes in the redox state [55,56,57]. The mechanisms of its redox sensitivity remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported the association of obesity with increased reabsorption of Na + in proximal tubules [59,60,61], impaired pressure natriuresis, and then hypertension [29]. Endogenous cardiotonic steroids (CTS) in humans and rodents [57,62], can signal through Na/K-ATPase, regulating renal salt handling in the proximal tubules [11,13,16] and contributing to salt-sensitive hypertension [12,15]. Since lithium (Li) is the marker for proximal tubular delivery [63], the data in this present study that correlates urinary total Na + and lithium excretion showed genuinely proportional excretion of both ions (Figure 2C), implicating identical handling of lithium and Na + in the proximal tubules in these two strains.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium-potassium adenosine triphosphatase (Na+/K+-ATPase) is an important membrane enzyme which plays a key role in cell structure and physiology by providing a sodium-potassium gradient in all cell membranes [20]. Tissue is the marker of viability during organ transplantation [20]. There is no study which adequately demonstrates the role of the Na+/K+-ATPase pump in the development of mesenteric I/R injury.…”
Section: Discussionmentioning
confidence: 99%